The effect of corporate social responsibility on debt finance: The moderating effect of accounting conservatism - Karim Mansour Ali; Emad sayed Abdel ghaffar (STIE Malangkucecwara, 2022)
This study aims to investigate the impact of corporate social responsibility (CSR) practices on the debt finance (DF) of Egyptian firms, as well as examine the moderating role of accounting conservatism (AC) on this relationship. The sample of the study consists of 120 listed Egyptian firms from 2012 to 2019 with overall observations of 960, the data were processed using the panel corrected standards errors (PCSE) and the generalized least squares (GLS). The results reveal that CSR practices have a negative effect on the DF of listed Egyptian firms, this means that listed firms that engage in CSR practices have less ability to obtain DF than non-CSR firms. Also, the results indicate that the negative effect of CSR practices on DF is more pronounced in firms that have a high conservatism. The results of this study have some essential implications, as CSR practices are crucial for stakeholders such as regulators, investors, and credit providers. Besides, this study contributes to testing some factors that affect firms' ability to obtain DF in one of the emerging countries such as Egypt. Keywords Corporate social responsibility, Debt finance, Accounting conservatism, Panel data, Egypt